2008
DOI: 10.1521/suli.2008.38.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Esteem and Suicide Ideation in Psychiatric Outpatients

Abstract: Depression, hopelessness, and low self-esteem are implicated as vulnerability factors for suicide ideation. The association of self-esteem with suicide ideation after controlling for depressed mood and hopelessness was examined. Adult psychiatric outpatients (N = 338) completed measures of self-esteem, suicide ideation, hopelessness, and depression. Self-esteem was operationalized as beliefs about oneself (self-based self-esteem) and beliefs about how other people regard oneself (other-based self-esteem). Each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 33 publications
3
72
0
7
Order By: Relevance
“…This finding is in accord with previous literature sampling populations across countries, communities, and psychiatric settings [3,8,23,26,37]. Two further studies, found that low levels of self-esteem were associated with suicidality in male [41], and female prisoners [50].…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in accord with previous literature sampling populations across countries, communities, and psychiatric settings [3,8,23,26,37]. Two further studies, found that low levels of self-esteem were associated with suicidality in male [41], and female prisoners [50].…”
Section: Discussionsupporting
confidence: 91%
“…Bursztein also emphasises the strong relationship between adolescent's aggression and impulsivity and suicide risk 24. Individuals with poorer school grades might run a higher risk for increased psychological stress and lower self-esteem, which alone is a well-known risk factor for suicide 2 3…”
Section: Discussionmentioning
confidence: 99%
“…School is an important arena in young persons' everyday life and success as well as failure may influence psychological stress and self-esteem—factors that are associated with suicide risk 2 3…”
Section: Introductionmentioning
confidence: 99%
“…8 Depression and hopelessness form a significant composite predictor of suicide ideation. 9 The present study aimed to examine both the rate and the risk factors of suicidal ideation among a group of depressed outpatients and to know the relation between the severities of depression, hopelessness with suicidal ideation.…”
mentioning
confidence: 99%